Pathophysiology‐Directed Engineering of a Combination Nanoanalgesic for Neuropathic Pain - Wenkai Wang; Yan Wang; Xinle Huang; Peng Wu; Lanlan Li; Yang Zhang; Yihui Chen; Zhiyu Chen; Changqing Li; Yue Zhou; Jianxiang Zhang (Advanced Science)
Abstract Neuropathic pain, one of the most refractory pain diseases, remains a formidable medical challenge. There is still an unmet demand for effective and safe therapies to address this condition. Herein, a rat model of nerve injury‐induced neuropathic pain is first established to explore its pathophysiological characteristics. Recognizing the role of neuroinflammation, an inflammation‐resolving amphiphilic conjugate PPT is designed and synthesized by simultaneously conjugating polyethylene glycol, phenylboronic acid pinacol ester, and Tempol onto a cyclic scaffold. PPT can self‐assemble into nanomicelles (termed PPTN). Following intravenous injection, PPTN preferentially accumulates in the injured nerve, ameliorates the neuroinflammatory milieu, and promotes nerve regeneration, thereby shortening neuropathic pain duration in rats. Moreover, the Ca2+ channel α2δ1 subunit is identified as a therapeutic target by RNA‐sequencing analysis of the injured nerve. Based on this target, a mimicking peptide (AD peptide) is screened as an analgesic. By packaging AD peptide into PPTN, a combination nano‐analgesic APTN is developed. Besides potentiated anti‐hyperalgesic effects due to site‐specific delivery and on‐demand release of AD peptide at target sites, APTN simultaneously inhibits neuroinflammation and promotes nerve regeneration by reprogramming macrophages via regulating MAPK/NF‐kB signaling pathways and NLRP3 inflammasome activation, thus affording synergistic efficacies in treating nerve injury‐induced neuropathic pain.